Indoor Localization Using K-Pairwise Light Emitting Diode Image-Sensor-Based Visible Light Positioning - Jenn-Kaie Lain; Lian-Cheng Chen; Sung-Chun Lin (IEEE Photonics Journal)
A great deal of research has been devoted to studying indoor localization schemes for the development of location-based services. This study investigated an indoor localization system, including subsystems of nonline-of-sight (NLOS) image-sensor-based visible light communications (IS-VLCs) and the proposed $K$ -pairwise light-emitting diode (LED) image-sensor-based visible light positioning (IS-VLP), in a unified lighting environment. A smartphone received multiple LED identifiers through the designed NLOS IS-VLC and successfully performed the proposed $K$ -pairwise LED IS-VLP with $K = 3$ to achieve localization, with maximum localization errors of 2.92 and 3.54 cm being obtained for ceiling heights of 100 and 150 cm, respectively.